The pedestrian in west Africa’s town, the poor parent of mobility in the Sahelian city of Ouaga-Dougou in Burkina Faso - Soma Assonsi; Yameogo Lassane (Glasnik Srpskog Geografskog Društva)
This article addresses the issue of pedestrian mobility in the city of Ouagadougou in Burkina Faso. The main objective is to identify the place given to pedestrians in urban mobility in this city. Specifically, the study aims to identify the daily movements of pedestrians in Ouagadougou, to analyse the impact of the occupation of public space, particularly the edges of the road, on pedestrian mobility and to better understand the sharing of traffic spaces for safe pedestrian mobility in this city. The methodological approach was based on two types of data sources. These concern the exploitation of administrative and scientific documents and the carrying out of a survey based on a questionnaire and semi-directive qualitative interviews with a sample of 115 people as well as field observations accompanied by the taking of photographs. It emerges that moving by foot every day in Ouagadougou is a major constraint for the wealthy or, above all, the poorest city dwellers. The spaces dedicated to pedestrians are either non-existent or occupied by other city dwellers using motorised means of transport to circulate or park or by commercial activities. Such a situation undoubtedly creates conflicts of use of these spaces, under the helpless gaze of the pedestrian and the local authority. This leads to the conclusion that the pedestrian is the poor relation of urban mobility in Ouagadougou. All in all, the study proposes to re-think the sharing of urban traffic spaces upstream by taking pedestrian mobility into account in urban planning policies and instruments, and downstream, to carry out mobility projects that take the pedestrian into account.